Compliance with Laws and Slaughterhouse Standards of Butcher’s Shops in North-Eastern Thailand - Muangsean, A.; Aengwanich, W. (Tropical Animal Science Journal, 2023)
The objective of this research is to study the characteristics of slaughterhouses and meat distribution of butcher’s shops operating under the relevant laws, including attitudes, problems, and obstacles facing butchers in implementing the law in the north-eastern part of Thailand. A total of 14 butcher shops at Baan Din Dam, Muang District, Maha Sarakham Province, participated in the study. Data were collected by surveying, interviews by using a semi-structured questionnaire, and focus group discussion. It was found that in cases where animals are slaughtered in standard slaughterhouses, butchers complied with the law. On the other hand, in the case of butchers who slaughtered animals by themselves, it was found that the practice mostly did not meet the standards as required by law. In terms of problems, obstacles, and attitudes of butchers regarding legal compliance, it was found that the butchers have knowledge related to law at a moderate level. They considered that the law was difficult to follow, but there was also a positive opinion that complying with the law gives consumers confidence and safety. Education level is the factor affecting opinions and attitudes on slaughter and meat distribution law. Compliance with butchers’ slaughter and meat distribution laws in north-eastern part of Thailand requires supervision from the government, and ongoing provision of education is necessary.